Relationship between oral stereognostic ability and dietary intake in older Japanese adults with complete dentures. Issue 1 (January 2019) - Fukutake, Motoyoshi; Ikebe, Kazunori; Okubo, Hitomi; Matsuda, Ken-ichi; Enoki, Kaori; Inomata, Chisato; Takeshita, Hajime; Mihara, Yusuke; Hatta, Kodai; Gondo, Yasuyuki; Kamide, Kei; Masui, Yukie; et al.
Abstract: Purpose: Oral stereognostic ability (OSA) is a useful indicator of oral perception to recognize food characteristics during mastication. Previous studies have shown associations between dietary intake and oral health status, such as taste perception. However, the effect of oral sensory ability on dietary intake is unclear. The purpose of this study was to investigate the association between oral sensory ability and dietary intake in older Japanese complete denture wearers. Methods: This cross-sectional study included 164 participants aged 69–71 or 79–81 years old, wearing both maxillary and mandibular complete dentures. OSA test was used to evaluate oral tactile perception. Diet during the preceding month was assessed using a self-administered diet history questionnaire. Multivariable linear regression analysis was conducted to assess the association between OSA score and food and nutrient intake after adjusting for age, sex, socioeconomic factors, and occlusal force. Results: The bivariate analysis showed that OSA score was significantly and positively correlated with intake of green and yellow vegetables and negatively correlated with intake of cereals among examined foods. OSA score was also positively correlated with intake of vitamins A, B2, and C and α-tocopherol (as a substitute for vitamin E) among examined nutrients. After adjusting for age, sex, socioeconomic factors, and occlusal force, OSA score remained significantly associated with intake of green and yellow vegetables and α-tocopherol. Conclusions: OSA was significantly associated with intake of green and yellow vegetables in older complete denture wearers.